PMD (PELATIHAN MEDIA DIGITAL) SEKTOR USAHA MIKRO DAN KECIL HANDYCRAFT BAMBU DI KAA SUKABUMI GUNA MENINGKATKAN PEMASARAN ONLINE BERBASIS MARKETPLACE DI ERA EKONOMI DIGITAL - Deri Firmansyah,; Asep Suryana,; Asep Achmad Rifa’i,; Dede Dr, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The purpose of implementing this community service is to provide digital media (PMD) training for the micro-business sector (UMi) and small-scale bamboo handicrafts (UK) businesses that are members of the Sukabumi KAA. The ultimate goal of each digital media training is to bring about changes that lead to improving the quality of human resources (HR) in terms of digital economic literacy for UMi and UK actors. The training is carried out with four stages of PDM program implementation activities, complemented by digital economic literacy materials and digital e-commerce and marketplace platforms. The results of the implementation of the PMD grant show that UMi and UK actors at the Sukabumi KAA who are partners and training participants have succeeded in creating and owning an online store account in the marketplace equipped with the ability to manage it properly that supports digital marketing activities to increase sales. It is hoped that MSMEs actors will truly become the pillars of the national economy who have good quality HR and business endurance, are able to develop and advance to class, and continue to be able to adapt in the midst of intense business competition in the digital ecosystem in the current digital economy era